1970
DOI: 10.1161/01.cir.41.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ultrasound Echoes from the Left Ventricle by Use of Intracardiac Injections of Indocyanine Green

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

1972
1972
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(36 citation statements)
references
References 10 publications
1
34
0
1
Order By: Relevance
“…Miniature bubbles, temperature differences, turbulence and fluid acoustic impedances have been explained as the sources of contrast echoes (Feigenbaum et al 1970;Seward et al 1977). Serwer et al (1978) reported that the most reproducible records were obtained by injection of echo-producing agents through either an 18 or 20 gauge indwelling catheter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miniature bubbles, temperature differences, turbulence and fluid acoustic impedances have been explained as the sources of contrast echoes (Feigenbaum et al 1970;Seward et al 1977). Serwer et al (1978) reported that the most reproducible records were obtained by injection of echo-producing agents through either an 18 or 20 gauge indwelling catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Gramiak et al (1969) used this method during cardiac catheterization and reported its usefulness for the first time. Several reports were thereafter made on this method (Feigenbaum et al 1970;Pieroni et al 1973; Kerber et al 1974; Seward et al 1975Seward et al , 1976Sahn et al 1977). However, it was not used widely on account of the technical difficulty of central venous injection.…”
mentioning
confidence: 99%
“…Gramiak and Shah later gave a presentation describing this new approach that fascinated Feigenbaum, who started investigating possible new clinical implications of contrast echocardiography. This discovery enabled examination of the characteristic of flow patterns in the presence of normal and abnormal cardiac hemodynamics (33). The potentially …”
Section: The Never-ending Quest For Better Imagingmentioning
confidence: 99%
“…The ability of certain materials to produce contrast enhancement in ultrasound images was first observed in the late 1960s by Dr. Claude Joyner whilst performing a study of cardiac output with the dye indocyanine green [31]. Subsequent investigation by Gramiak and Shah [32] and Kremkau et al [33] demonstrated that it was not the dye itself that was the source of the effect, but rather the formation of gas bubbles at the catheter tip.…”
Section: Evolution Of Microbubble Agentsmentioning
confidence: 99%